DEVELOPMENT OF PINKI (INDONESIAN CULTURE INTERACTIVE BOARD) WITH STRENGTHENING THE CURIOSITY OF CLASS IV STUDENTS - Damayanti, Susan; Mas’ula, Siti; Putra, Arda Purnama (Universitas Pendidikan Indonesia, 2024)
The development of PINKI learning media aims to produce learning media that are valid, practical and effective in strengthening one of students' curiosity. Combined with the presence of technology in it can make this learning media interactive. This development uses the RD method and the ADDIE development model. Data collection techniques were carried out by interviewing, observing and giving questionnaires to material experts, media experts and teachers. While the technique of collecting data students are given questionnaires and questions. The validation results from validator 1 reached an average percentage of 92.87%, validator 2 achieved an average percentage of 96.52% with a very valid category of all validators. The practicality of students is 98.38% and that of teachers is 100.00% so that it is in the very practical category. The processing results of the data normality test were normally distributed, and the results of the paired sample t test sig (2-tailed) were 0.000 0.05 with a decision finding found significant differences in the learning process before and after using PINKI learning media. Thus, the PINKI learning media was stated to be very valid, very practical and effective in strengthening students' curiosity so that it could be used in the process of learning cultural diversity material in class IV East Java Province.